Exploration of an XX/XY Sex Determination System and Development of PCR-Based Sex-specific Markers in Procambarus clarkii Based on Next-Generation Sequencing Data - Shen, Yudong; Wang, Qishuai; Wang, Weimin; Li, Yanhe (Frontiers in Genetics, 2022)
Many economic crustacean species have sex dimorphisms during their growth. Exploring the sex determination system and developing sex-specific molecular marker(s) are very helpful for carrying out the sex control breeding, and next-generation sequencing has been used as an efficient way to explore them in recent years. In this study, firstly, the genetic sex determination system of P. clarkii was explored as XX/XY system by analyzing the 2b-RAD sequencing data. Furtherly, DNA samples of male and female individuals from a P. clarkii family were pooled separately for whole genome resequencing. Based on the data of whole genome resequencing, the 9,163 male and female specific bias sites with higher feasibility were obtained based on the assumption of XX/XY sex determination system, and four sites were selected to design the sex specific marker primers. One efficient sex-specific marker was identified as the sex discrimination rate of 99.49% (195/196) when applied to five different geographical groups with 196 individuals. The results of this study would provide a foundation for realization of P. clarkii sex control, and could provide some reference for investigating sex determination system and sex molecular marker(s) of other crustacean species based on next-generation sequencing data.